Death receptors in chemotherapy and cancer - Debatin, Klaus-Michael; Krammer, Peter H. (Oncogene, 2004)
Apoptosis, the cell's intrinsic death program, is a key regulator of tissue homeostasis. An imbalance between cell death and proliferation may result in tumor formation. Also, killing of cancer cells by cytotoxic therapies such as chemotherapy, γ-irradiation or ligation of death receptors is predominantly mediated by triggering apoptosis in target cells. In addition to the intrinsic mitochondrial pathway, elements of death receptor signaling pathways have been implied to contribute to the efficacy of cancer therapy. Failure to undergo apoptosis in response to anticancer therapy may lead to resistance. Also, deregulated expression of death receptor pathway molecules may contribute to tumorigenesis and tumor escape from endogenous growth control. Understanding the molecular events that regulate apoptosis induced by anticancer therapy and how cancer cells evade apoptosis may provide new opportunities for pathway-based rational therapy and for drug development.
Gesehen am 02.03.2021